2012
DOI: 10.1007/s10853-012-6934-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the relative humidity on the fibre morphology of polyamide 4.6 and polyamide 6.9 nanofibres

Abstract: To obtain uniform and reproducible nanofibres, it is important to understand the effect of the different electrospinning parameters on the nanofibre morphology. Even though a lot of literature is available on the electrospinning of nanofibres, only minor research has been performed on the effect of the relative humidity (RH). This paper investigates the influence of this parameter on the electrospinning process and fibre morphology of the hydrophilic polyamide 4.6 and the less hydrophilic polyamide 6.9. First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Therefore, when water molecules were absorbed in the PA 6 matrix, the α 2 crystal structure (hydrogen bonding between the sheets of crystal chains) was compressed by the expanded the amorphous crystalline due to the water molecules. The α 1 crystal structure (distance of the crystal chain) was not affected . This clearly indicates that the flame treatment contributed to enhance the stability of the crystal structure of the PA 6 matrix of CFRTP during the T‐RTM process by eliminating the moisture on the carbon fiber.…”
Section: Resultsmentioning
confidence: 88%
“…Therefore, when water molecules were absorbed in the PA 6 matrix, the α 2 crystal structure (hydrogen bonding between the sheets of crystal chains) was compressed by the expanded the amorphous crystalline due to the water molecules. The α 1 crystal structure (distance of the crystal chain) was not affected . This clearly indicates that the flame treatment contributed to enhance the stability of the crystal structure of the PA 6 matrix of CFRTP during the T‐RTM process by eliminating the moisture on the carbon fiber.…”
Section: Resultsmentioning
confidence: 88%
“…The humidity has significant influence on the rate of solvent evaporation, which in turn affects the surface morphology of the electrospun nanofibers . Casper et al demonstrated that the number of pores and pore size on the surface of polysulfone nanofibers increased as the humidity increased, as shown in Figure .…”
Section: Electrospinning Methodsmentioning
confidence: 99%
“…The large nanofibrous membranes were electrospun at 23 ± 2 ºC and 50 ± 10 % RH. mass and humidity are the major electrospinning parameters that affect fibre diameter [16][17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%